Pengaruh Permainan Tradisional Das Terhadap Kemampuan Matematika Permulaan - Sharna Mellisa Dhasni; Budi Kurniawati, Asih; Devi Nawangsasi (Jurnal Kajian Anak (J-Sanak), 2025)
The problem in the study is the initial mathematical ability of children aged 5-6 years who still need appropriate stimulation according to the age and abilities of the child. This study aims to determine the effect of traditional das games on the initial mathematical ability of children aged 5-6 years. This study uses a quantitative research type with a pre-experimental method and a one group pretest-posttest design. The sample in this study amounted to 29 children aged 5-6 years. The sampling technique used a purposive sampling technique. The data collection technique used was observation carried out using an observation sheet that had been tested for validity and reliability and was declared valid and reliable. The research data was tested using the Paired Sample Test and obtained a value of 0.000. This value is less than 0.05 (0.000 <0.05), which means that there is a positive influence between traditional das games on the initial mathematical ability of children aged 5-6 years. This positive influence is because the traditional das games used can attract children's interest and are carried out repeatedly, so that it is in line with Piaget's theory which states that children's activities that are carried out repeatedly will create new knowledge for children.